Changing Contexts, Shifting Meanings Transformations of Cultural Traditions in Oceania - Hermann, Elfriede (University of Hawaii Press, 2011)
Finally, two authorities on Oceania—who themselves move in the intersecting space between anthropology and history—discuss the essays and add their own valuable reflections.With its wealth of illuminating analyses and illustrations, Changing Contexts, Shifting Meanings will appeal to students and scholars in the fields of cultural and social anthropology, history, art history, museology, Pacific studies, gender studies, cultural studies, and literary criticism.Contributors: Aletta Biersack, Françoise Douaire-Marsaudon, Bronwen Douglas, David Hanlon, Brigitta Hauser-Schäublin, Peter Hempenstall, Margaret Jolly, Miriam Kahn, Martha Kaplan, John D. Kelly, Wolfgang Kempf, Gundolf Krüger, Jacquelyn Lewis-Harris, Lamont Lindstrom, Karen Nero, Ton Otto, Anne Salmond, Serge Tcherkézoff, Paul van der Grijp, Toon van Meijl